Application of the thermally insulating medical bandage in complex treatment of patients with cold injury - Shapoval, Elena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To study the effectiveness of using of thermally insulating medical bandage (рat. 72350, Ukraine) in treatment of patients with cold injury. Methods: We investigated an incidence of local complications in 62 patients with cold injury and a mean age of 36 years. For the patients in the group I (n = 17) the first aid was provided in 1–2 hours after the onset of low temperature action, in the II (n = 16) — from 3 to 6 hours, and in the III (n = 19) — after 6 hours or more. In patients (n = 10) of the control group in before reacting period we did not use any thermally insulating bandages. In patients of all groups we performed infusions and medication therapy. Results: frostbites of II–IV degree have been formed for all the victims whom first aid was provided within the period from the beginning of long-term cold exposure in. One of the risk factors for the formation of deep frostbite was absence of using of thermal insulating bandages in before reacting period. Due to the high thermal insulation properties of the application an original thermally insulating medical bandage in complex treatment of patients with a cold trauma there were achieved required effect of protection of the superficial areas in the affected limbs from warming from outside with slow recovery of blood circulation by improving the microcirculation in tissues. Transparency of the thermally insulating medical bandage allowed constant visual monitoring of the damaged areas. Conclusion: The analysis of the efficiency and quantitative assessment of outcomes allow to ascertain the feasibility of using on thermally insulating medical bandage in the complex treatment of patients with cold injury in the pre-hospital and hospital stages of medical care.